2022
DOI: 10.1038/s41467-022-29401-6
|View full text |Cite
|
Sign up to set email alerts
|

USP8 inhibition reshapes an inflamed tumor microenvironment that potentiates the immunotherapy

Abstract: Anti-PD-1/PD-L1 immunotherapy has achieved impressive therapeutic outcomes in patients with multiple cancer types. However, the underlined molecular mechanism(s) for moderate response rate (15–25%) or resistance to PD-1/PD-L1 blockade remains not completely understood. Here, we report that inhibiting the deubiquitinase, USP8, significantly enhances the efficacy of anti-PD-1/PD-L1 immunotherapy through reshaping an inflamed tumor microenvironment (TME). Mechanistically, USP8 inhibition increases PD-L1 protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 55 publications
2
60
0
Order By: Relevance
“…It has been suggested that inhibition of USP8 increases PD-L1 protein abundance and activates NF-κB signaling to trigger innate immune responses and MHC-I expression. Combining USP8 inhibitors with PD-1/PD-L1 blockers inhibited tumor growth and improved survival in CC mouse model ( 51 ). Conversely, high levels of USP8 may lead to T cell dysfunction, consistent with our results that USP8 is a risky factor and its expression is negatively correlated with CD8 + T cells ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that inhibition of USP8 increases PD-L1 protein abundance and activates NF-κB signaling to trigger innate immune responses and MHC-I expression. Combining USP8 inhibitors with PD-1/PD-L1 blockers inhibited tumor growth and improved survival in CC mouse model ( 51 ). Conversely, high levels of USP8 may lead to T cell dysfunction, consistent with our results that USP8 is a risky factor and its expression is negatively correlated with CD8 + T cells ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Combining USP8 inhibitors with PD-1/PD-L1 blockers inhibited tumor growth and improved survival in CC mouse model ( 51 ). Conversely, high levels of USP8 may lead to T cell dysfunction, consistent with our results that USP8 is a risky factor and its expression is negatively correlated with CD8 + T cells ( 51 , 52 ). UBE2B , UBE2G2 , UBE2E2 and UBE2K are all E2 ubiquitin-conjugating enzymes and E2s are classified into four different types ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…CC[ 99 ], colon cancer[ 100 ], melanoma[ 101 , 102 , 106 ], lung cancer[ 101 ], esophageal squamous cell carcinoma[ 105 ]…”
Section: Micrornasmentioning
confidence: 99%
“…LPS or high-cholesterol diet (HCD)-induced macrophage infiltration significantly activates the C-C motif chemokine ligand 5 (CCL5)-P65/STAT3-CSN5-PD-L1 signaling pathway in azoxymethane-induced CC mouse models and is correlated with poor prognosis [ 99 ]. In contrast to CSN5, the deubiquitinase USP8 removes TNF receptor associated factor 6 (TRAF6)-mediated K63-linked ubiquitination, thereby promoting PD-L1 degradation in mouse models of lung and colon cancer [ 100 ]. Ubiquilin 4 (UBQLN4) suppresses PD-L1 ubiquitination and promotes protein stability in melanoma.…”
Section: Ubiquitinationmentioning
confidence: 99%
See 1 more Smart Citation